Human capital, religiosity, and participatory governance as drivers of welfare through rural–urban linkages in Cirebon Regency - Bakhri, Syaeful; Fanther, Refaldo; Ma'ruf, Amar; Zahra, Dinar Maula (Universitas Islam Indonesia, 2026)
IntroductionCommunity welfare in border regions is shaped by complex interactions among demographic conditions, religiosity, governance, and rural–urban economic linkages. Despite growing attention to rural–urban development, previous studies have largely examined these factors independently, providing limited understanding of how they collectively influence welfare in decentralized regions. Integrating perspectives from rural–urban development and Islamic economics offers a more comprehensive framework for explaining sustainable and inclusive community welfare.ObjectivesThis study aims to examine the effects of demographic factors and religiosity on community welfare in the border areas of Cirebon Regency, Indonesia. It also seeks to develop an integrated rural–urban development model by identifying strategic priorities for sustainable welfare improvement from the perspectives of human capital, participatory governance, and Islamic economics.MethodThis study employed a convergent parallel mixed-methods design. Quantitative data were collected from 156 respondents across four border subdistricts using structured questionnaires and analyzed through multiple linear regression to examine the effects of demographic factors and religiosity on community welfare. Qualitative data were obtained through observations, interviews, documentation, and focus group discussions to explore rural–urban interactions and institutional dynamics. The Analytic Hierarchy Process was subsequently applied to determine the priority of sustainable livelihood assets supporting community welfare.ResultsThe findings demonstrate that demographic factors and religiosity both exert significant positive effects on community welfare, with religiosity emerging as the stronger predictor. Human capital, particularly education and health, represents the highest strategic priority for sustainable development, followed by financial and physical capital. The qualitative findings further indicate that participatory governance, institutional collaboration, and balanced rural–urban economic linkages strengthen social cohesion, improve access to economic opportunities, and reduce regional disparities. From an Islamic economics perspective, these outcomes are consistent with the principles of maqāṣid al-sharīʿah, which emphasize human development, social justice, and collective welfare through ethical governance and inclusive economic participation.ImplicationsThe study highlights the importance of integrating human capital development, participatory governance, Islamic social finance, and rural–urban connectivity into regional development policies. Such an integrated approach can strengthen community resilience, promote equitable welfare distribution, and support sustainable territorial development in border regions.Originality/NoveltyThis study proposes an integrated framework that combines demographic factors, religiosity, rural–urban economic linkages, governance, and Islamic economics to explain community welfare. By integrating quantitative and qualitative evidence within a single analytical model, it provides a novel contribution to the literature on sustainable regional development and offers practical policy guidance for border areas in Indonesia and other developing economies.